(untitled) (Fiep Bulletin - online, 2015)
The game has an important educational role in the child’s life as a citizen who will be developing, knowing the world , interacting and building from social exchanges that will establish . The present study with descriptive characteristic of a case study aimed to analyze the game as a tool in interpersonal relationships of children in the Children’s perception of teachers teaching the Diocesan College Santa Luzia , in the Mossoró City -RN . Type of structured interview was used as a tool for data collection. The results indicate that the game , in the opinion of teachers investigated , can be used in the interpersonal relationships of children of kindergarten , because it is an important and necessary tool for child development in the aspects , motor , intellectual , social , psychological , values ??triggering the formation of his character , thus facilitating group work , the cooperativity , affectivity and social interaction of children.